Diversifikasi Usaha Dan Pengaruh Terhadap Pendapatan Petani Padi Sawah Pasca Kerusakan Bendungan Irigasi Krueng Pasee di Desa Keutapang Kecamatan Syamtalira Aron - Riani Riani; Suryadi Suryadi; Barmawi Barmawi; Salamah Salamah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
The damage to the Krueng Pasee irrigation dam caused a decline in wet-rice production in North Aceh Regency, decreasing from 427,455 tons in  2019 to 388,190 tons in 2021. However, some  farmers   continued  farming by  adjusting to the rainy season. Meanwhile, other  farmers  chose  not to  engage  in agricultural  activities   during the  dry season, requiring  strategies to  sustain their  livelihoods   through  business diversification as an additional source of income. This study aims to  identify the types of business  diversification  and  the factors  influencing  the income of wet-rice farmers after the irrigation dam damage. The research  area was determined using purposive sampling. A total of 30 farmers were  selected as samples  using a simple random  sampling technique. Data were  analyzed using qualitative  descriptive  analysis to describe  the business diversification carried out by wet-rice  farmers, while the influence of farmer characteristics on income was analyzed using quantitative descriptive analysis with multiple linear regression. The results showed that wet-rice  farmers in Keutapang Village engaged in two types of business diversification: non-rice farming  and non-farm businesses. The average  monthly  income  obtained from alternative non-farm  sources was higher  than that from  non-rice  farming   activities  because  the village is located close to  the sub-district capital,  making  it easier for  farmers to work outside agriculture by offering services or trading. The variables  of gender and  experience in  alternative jobs had a significant effect  on alternative income, while age and education variables had no significant effect on income.